1996
DOI: 10.1287/moor.21.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Interior Point Algorithms for the Monotone Linear Complementarity Problem

Abstract: The literature on interior point algorithms shows impressive results related to the speed of convergence of the objective values, but very little is known about the convergence of the iterate sequences. This paper studies the horizontal linear complementarity problem, and derives general convergence properties for algorithms based on Newton iterations. This problem provides a simple and general framework for most existing primal-dual interior point methods. The conclusion is that most of the published algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 22 publications
1
32
0
5
Order By: Relevance
“…The superlinear convergence of the duality gap for the feasible largest step algorithm was first proved by McShane [12] for nondegenerate monotone SLCPs under the assumption that the iteration sequence converges. The results of Bonnans and Gonzaga [2] show that this assumption holds. The largest step method was extended for the infeasible case by Bonnans and Potra [4].…”
Section: Applicationsmentioning
confidence: 84%
See 2 more Smart Citations
“…The superlinear convergence of the duality gap for the feasible largest step algorithm was first proved by McShane [12] for nondegenerate monotone SLCPs under the assumption that the iteration sequence converges. The results of Bonnans and Gonzaga [2] show that this assumption holds. The largest step method was extended for the infeasible case by Bonnans and Potra [4].…”
Section: Applicationsmentioning
confidence: 84%
“…Gonzaga and Tapia [10] also proposed a modification of the MTY predictor-corrector method (called the simplified MTY method) that asymptotically requires only one matrix factorization per iteration while retaining the O( √ n L) iteration complexity and the Q-quadratic convergence of the duality gap, and showed that the iteration sequence produced by this method converges, but not necessarily to the analytic center. The above results about the convergence of the iteration sequence were extended for a very general class of feasible interior-point methods by Bonnans and Gonzaga [2] and generalized for infeasible interior-point methods by Bonnans and Potra [4]. From the last two papers it follows that virtually all interior-point methods using an l 2 neighborhood of the central path produce convergent iteration sequences.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…MTY was generalized to (monotone) LCP in [8], and the resulting algorithm was proved to have O( √ nL) iteration complexity under general conditions and superlinear convergence, under the assumption that the LCP has a strictly complementary condition (i.e., when the LCP is nondegenerate) and the iteration sequence converges. From [3] it follows that the latter assumption always holds. Subsequently Ye and Anstreicher [19] proved that MTY converges quadratically assuming only that the LCP is nondegenerate.…”
Section: Introductionmentioning
confidence: 90%
“…Its extension for the HLCP is immediate, using for example the equivalences proved in [1] (see also [3]). …”
Section: Theorem 32 If Hlcp (21) Is Monotone Then Algorithm 1 Is Wementioning
confidence: 96%